Exact confidence limit for complex system reliability based on component test data. Issue 1 (2nd January 2020) - Du, Senyao; Li, Zhaohui; Yu, Dan; Li, Dongmin; Hu, Qingpei
ABSTRACT: Reliability analysis for complex system is one of the most concerned problems in industry. On account of high cost of testing we often obtain a small size of sample, even only test data for components. In this article, an exact method for system reliability assessment will be presented generalized from the Buehler confidence limit. We give a suggestion on the choice of statistic order based on an estimate of system reliability which only relies on the true value of even for multiparameter model. In addition, we present an algorithm to solve the function with constraint set up in Buehler method. A three-component application is given to illustrate the algorithm. We also present some simulation studies to compare our proposed method with other widely applied methods.